Speech Acts and Politeness Strategies on Student’s Conversation at SMPN 3 Binjai - Metty Asima Panggabean; Erika Sinambela; Lastri W. Manurung (UIBU, 2023)
The study's goal is to pinpoint the manners and speech patterns used by SMP N 3 Binjai students. Analytical qualitative analysis was employed by the researcher. Students were the research subject. The research instrument was observation. This study design was based on descriptive qualitative research. The most prevalent speech act utilized by the English instructor and pupils at SMP N 3 Binjai during instruction and learning in the classroom is a directive speech act, according to the conclusion reached through the data analysis procedure. The researcher found 104 utterances were identified as Politeness, 38 as Positive Politeness, and 30 indirect Politeness. It means that 75% of them are positive politeness utterances and 16% are negative politeness, According to the discussion above, it can be stated that Positive Politeness is the predominant form of politeness utilized by students at SMP N 3 Binjai during the teaching and learning process in the classroom. The researcher found that the percentage of the most dominant speech act used by students was 40 % for Directive within 38 frequency utterances and the second Assertive speech act was 33 % within 34 frequency and the total percentage was 73 %. The researcher concluded the most dominant Speech act was the Directive. The findings suggest that Mark Rutte employs a positive rather than a negative politeness style. It is a sign that Mark Rutte wishes to approach or treat his recipient like a friend by employing more considerate manners